2022
DOI: 10.53294/ijfcpr.2021.1.1.0054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of alkalinity on the adsorption of cadmium ion using KOH-activated carbon from Sesame stem

Abstract: The increase alkalinity on the adsorption of cd2+ using KOH-activated carbon from Sesame stem was studied. Determination of metal ion in solution shows adsorption capacities of 86.68 % for KOH-AC at saturated state. Effect of metal ion concentration shows that, Removal efficiency of Cd2+ by KOH-AC increases with increasing presence of the adsorbate due to the availability of adsorption sites on the activated carbon. Increase acidity general favors the adsorption. The effect of pH shows that the adsorption of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…To investigate the initial metal ion concentration on sorption capacity, different sample consisting of 50 ml of the metal ion concentration from 10ppm, 20ppm, 40 ppm, 60 ppm, 100 ppm, but each containing 2g activated carbon sesame stem were prepared and shaken for 1hour until equilibrium was obtain. The synthetic wastewater was filtered and analyzed for residual metal ion concentration using AAS [10].…”
Section: Effect Of Initial Metal Ion Concentration On Sorption Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the initial metal ion concentration on sorption capacity, different sample consisting of 50 ml of the metal ion concentration from 10ppm, 20ppm, 40 ppm, 60 ppm, 100 ppm, but each containing 2g activated carbon sesame stem were prepared and shaken for 1hour until equilibrium was obtain. The synthetic wastewater was filtered and analyzed for residual metal ion concentration using AAS [10].…”
Section: Effect Of Initial Metal Ion Concentration On Sorption Capacitymentioning
confidence: 99%
“…From Figure 1, it was observed that HNO3 activated carbon shows a significant sorption of 84.48 % of the cadmium ions. Mikyitsabu et al, [10] studied the sorption of sesame stem by KOH-AC, the result show that the equilibrium adsorption was attained after about 1 hour with adsorption capacities of 84.48 KOH-AC. Aghdas et al [11] revealed the impregnation ratio of the activating agent which highly influenced the surface area and the porosity development during preparation.…”
Section: Effect Of Sorption Capacity Of Cadmium Using Hno3-acmentioning
confidence: 99%
See 1 more Smart Citation